The processing of formulaic language - Conklin, Kathy; Schmitt, Norbert (Cambridge University Press, 2012)
It is generally accepted that we store representations of individual words in our mental lexicon. There is growing agreement that the lexicon also contains formulaic language (How are you? kick the bucket). In fact, there are compelling reasons to think that the brain represents formulaic sequences in long-term memory, bypassing the need to compose them online through word selection and grammatical sequencing in capacity-limited working memory. The research surveyed in this chapter strongly supports the position that there is an advantage in the way that native speakers process formulaic language compared to nonformulaic language. This advantage extends to the access and use of different types of formulaic language, including idioms, binomials, collocations, and lexical bundles. However, the evidence is mixed for nonnative speakers. While very proﬁcient nonnatives sometimes exhibit processing advantages similar to natives, less proﬁcient learners often have been shown to process formulaic language in a word-by-word manner similar to nonformulaic language. Furthermore, if the formulaic language is idiomatic (where the meaning cannot be understood from the component words), the ﬁgurative meanings can be much more difﬁcult to process for nonnatives than nonidiomatic, nonformulaic language.